PARENTING SELF-EFFICACY BASED ON STIFIN AS INTELLEGENCE MECHINE OF LEARNING - Diana, Eka; Sholehah, Siti Wardatus (Nurul Jadid University, 2022)
This article describes parenting through the STIFIn method in building the confidence of students in the Al-Mawaddah area of the Pesantren Nurul Jadid Paiton. Self-confidence in this case is more about the students' belief in their ability to deal with something. This is certainly very influential on the development of its potential in the future. This research uses a qualitative case study approach. Sources of data in this study obtained through observation and interviews. Sampling of informants used purposive sampling technique which was then determined to number five of them were administrators as well as guardians of Al-Mawaddah Pondok Pesantren Nurul Jadid. This study obtained the results that the application of the STIFIn method in building self-confidence in students through several stages, namely; 1) Genetic potential test; 2) Classification of the relationship between foster guardians and foster children; and 3) Determining Potential Genetic-Based Parenting Patterns.